2007
DOI: 10.1111/j.1475-6811.2006.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Adoption, attachment, and relationship concerns: A study of adult adoptees

Abstract: Given ongoing controversy regarding the psychosocial adjustment of adoptees, this study examined the impact of adoptive status and family experiences on adult attachment security, and the role of attachment in predicting relationship outcomes. Adults who were adopted as infants (N = 144), and a comparison sample of nonadoptees (N = 131), completed measures of attachment security at recruitment and again six months later; other measures assessed parental bonding and adoptees' reunion experiences (Time 1), and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
55
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 51 publications
7
55
1
2
Order By: Relevance
“…Participants were 18 adult adoptees (15 females and 3 males) who had taken part in a larger study comparing 144 adoptees and 131 non-adoptees (see Feeney, Passmore, & Peterson, 2007 for more detail about the larger study). These 18 participants were chosen because they were the only ones who had met both their birth mother and their birth father.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Participants were 18 adult adoptees (15 females and 3 males) who had taken part in a larger study comparing 144 adoptees and 131 non-adoptees (see Feeney, Passmore, & Peterson, 2007 for more detail about the larger study). These 18 participants were chosen because they were the only ones who had met both their birth mother and their birth father.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Some studies compared adopted and non-adopted young adults, mainly focusing on mental health and psychological well-being; however, results of these studies are not consistent and have exhibited contradictory findings. On one hand, a number of studies demonstrated that adult adoptees are more likely to be at higher risk for psychopathological outcomes and lower level of psychological well-being (Cubito & Obremski Brandon, 2000;Cantor-Grace & Pedersen, 2007;Feeney, Passmore, & Peterson, 2007;Hjern, von Borczyskowski, Lindblad, & Vinnerljung, 2006;Levy-Shiff, 2001;Passmore, Fogarty, Bourke, & Baker-Evans, 2005;Tieman, van der Ende, & Verhulst, 2005), while other studies failed to find any differences in adjustment and in psychological wellbeing between adopted and non-adopted adults (Borders, Penny, & Portnoy, 2000;Feigelman, 2000;Irhammar & Bengtsson, 2004;Kelly, Towner-Thyrum, Rigby, & Martin, 1998;Smyer, Gatz, Simi, & Pedersen, 1998).…”
mentioning
confidence: 97%
“…Baden and Wiley (2007) cite research supporting that adoption issues are mediated not only by intrapsychic variables but also relationships with significant others and the broader society. In the following excerpt, Feeney, Passmore, and Peterson (2007) point out possible cultural influences on the adoption experience and narrative:…”
Section: Introductionmentioning
confidence: 99%